Recognition of left ventricular hypertrophy in new recruits of professional sumow restling - Kinoshita, N.; Onishi, S.; Yamazaki, H.; Katsukawa, F. (Journal of Science and Medicine in Sport, 2003)
The efficacy of electrocardiography (ECG) in the diagnosis of left ventricular (LV) hypertrophy in 890 males, newly recruited to Japanese professional sumo wrestling (15.9 +/- 1.8 years of age, 177.8 +/- 4.7cm, 107.3 +/- 4.7kg), was tested by comparing simple, widely employed ECG criteria (Sokolow-Lyon chest and limb lead voltages and Cornell voltage with repolarisation criteria) with echocardiographic evaluations of LV mass indexed to body surface area. LV hypertrophy was defined as a LV mass index > 2 SD above the mean value obtained from 115 age-matched, normotensive, sedentary, male controls. The prevalence of LV hypertrophy as determined by echocardiography was 9.0% the entire group and was 8.3% among the 484 normotensives. The sensitivities of the three ECG criteria were < or = 36.0%, and their specificities were 70.0-99.0%. In contrast to the Sokolow-Lyon chest lead criteria, the diagnostic performance of the Cornell criteria was little affected by body mass index (BMI), and stepwise regression revealed that BMI did not significantly correlate with Cornell voltage. Still, the diagnostic efficacy of ECG was not sufficient to merit its use for primary recognition of LV hypertrophy among professional sumo wrestlers. Indeed, LV hypertrophy will likely go undetected by ECG in most overweight muscular athletes.